PREVALENCE OF STOMATITIS IN ANAEMIC PATIENTS- AN INSTITUTION BASED RETROSPECTIVE STUDY - Krishna R, Nivesh; Kumar Vadive, Jayanth; S, Arvind (International Journal of Psychosocial Rehabilitation, 2020)
One of the most common oral manifestations of anemia is anemic stomatitis. Stomatitis refers to inflammation of the mouth and lips. In other words, it's an inflammatory process that affects the mucous membrane of the mouth and lips. The term stomatitis is derived from a Greek word in which “stoma” refers to mouth and “itis” refers to inflammation. Anemia is a global hematological disorder affecting people of almost all the age groups. It is estimated that almost one-third of the world’s population is anemic and are affected by one or other anemic disorder. These disorders are mainly caused due to nutritional deficiencies that occur due to malnourishment or due to chronic intake of an imbalanced diet. The aim of this study was to determine the prevalence of stomatitis in patients with anemia. About 86000 records of the patients were obtained and screened for the presence of anemia. In this study, 47 patients who self-reported with anemia were chosen. Among the 47 patients, 23 were male patients and 24 were female patients. This indicates that the predominant gender was female. To estimate the predominant age group affected by anemia and anemic stomatitis, the patients were divided into three groups. Group 1 includes 18-35 years; group 2 includes 36-50 years and group 3 includes 51-70 years of age. Both anemia and anemic stomatitis was predominantly seen among group 2 patients (36-50 years of age). 13 patients who were diagnosed with anemic stomatitis, in the group of anemia patients. It was estimated that anemic stomatitis was present in 27.7% of the study population. The association was performed with a chi-square test to associate between age, gender and anemic stomatitis and a significant association was reported.